The Influence of Project Leader and SDGs Implementation on Project Success with Management Transformation as a Mediating Variable - Marbun, Pahala Budiman; Nugroho, Rosalendro Eddy (International Journal of Social and Management Studies, 2025)
Abstract - This study examines the effects of Project Leader and SDGs implementation on housing project success, with Management Transformation as mediator. A cross-sectional survey was administered; 150 valid responses were analyzed. Data were collected using structured questionnaires and processed with PLS-SEM two-stage model. Results show all paths significant at α < 0.05. Project Leader directly affects project success and indirectly through Management Transformation. SDGs implementation influences Management Transformation and also increases project success. Management Transformation positively affects project success. Mediation tests confirm Management Transformation mediates the effects of Project Leader and SDGs implementation. These findings highlight the roles of leadership, sustainability, and management transformation in improving housing project performance.